Associations across food consumption, diabetes prevalence and the environmental impacts: Evidence from China - Bingtao Su; Xianqiang Cao (PLoS ONE, 2025)
Dietary choices are shifting globally in ways that are directly affecting both the environment and human health. Building on the Diabetes Epidemiological Survey, and the latest data from the China Statistical Yearbook, this study quantified Chinese people’s dietary ecological footprint per capita (EFP) and the greenhouse gas (GHG) emissions at the provincial level with different prevalence of diabetes and prediabetes. Results demonstrated that groups with a lower prevalence of diabetes showed lower dietary EFP, while the dietary EFP and GHG emissions peaked among the prediabetes group with a prevalence of 32.7%−34.9%, and then decreased significantly with the increasing prevalence of prediabetes. The increasing prevalence of diabetes was tightly linked to increased consumption of pork, poultry, seafood, eggs, and vegetables. Moreover, the over-consumption of meat, oil, and cereal, together with the under-consumption of vegetables, fruits, eggs, and milk, will further increase both the prevalence of diabetes and environmental degradation. Yet, people’s concern for their health will drive them to pursue a healthier diet, which in turn will promote environmental sustainability. Findings in this study can help to reshape the dietary patterns that can effectively reduce the environmental and health impacts not only in China but also in other countries with accelerated diet-environment-health trilemma.